Morphological characteristics of lesions with thin cap fibroatheroma—a substudy from the COMBINE (OCT-FFR) trial. (7th November 2022) - Roleder-Dylewska, Magda; Gasior, Pawel; Hommels, Tobias M; Roleder, Tomasz; Berta, Balasz; Ang, Hui Ying; Ng, Jaryl Chen Koon; Hermanides, Renicus S; Fabris, Enrico; IJsselmuiden, Alexander J J; Kauer, Floris; Alfonso, Fernando; et al.
Abstract: Aims: To study if any qualitative or quantitative optical coherence tomography (OCT) variables in combination with thin cap fibroatheroma (TCFA) patients could improve the identification of lesions at risk for future major adverse cardiac events (MACEs). Methods and results: From the combined optical coherence tomography morphologic and fractional flow reserve hemodynamic assessment of non- culprit lesions to better predict adverse event outcomes in diabetes mellitus patients: COMBINE (OCT-FFR) trial database (NCT02989740), we performed a detailed assessment OCT qualitative and quantitative variables in TCFA carrying diabetes mellitus (DM) patients with vs. without MACE during follow-up. MACEs were defined as a composite of cardiac death, target vessel myocardial infarction, clinically driven target lesion revascularization, and hospitalization for unstable angina. From the 390 fractional flow reserve (FFR)-negative DM patients, 98 (25.2%) had ≥1 OCT-detected TCFA, of which 13 (13.3%) had MACE and 85 (86.7%) were event-free (non-MACE). The baseline characteristics were similar between both groups; however, a smaller minimal lumen area (MLA) and lower mean FFR value were observed in MACE group (1.80 vs. 2.50 mm 2, P = 0.01, and 0.85 vs . 0.89, P = 0.02, respectively). Prevalence of healed plaque (HP) was higher in the MACE group (53.85 vs. 21.18%, P = 0.01). TCFA were predominantly located proximal to the MLA. TCFA area was smaller in the MACE group, while no difference was observed regarding the lesion area. Conclusion: Within TCFA carrying patients, a smaller MLA, lower FFR values, and TCFA location adjacent to a HP were associated with future MACE. Carpet-like measured lesion area surface was similar, while the TCFA area was smaller in the MACE arm, and predominantly located proximal to the MLA. Graphical Abstract: Graphical Abstract